Understanding Taxpayer Perspectives on The Tax System and the Fairness of Tax Evasion Behavior: The Mediating Role of Tax Compliance - Nurfauziah, Farah Latifah; Nurjuhariyah, Nurjuhariyah (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2023)
Tax evasion is an action taken to avoid tax burdens by being payable illegally by hiding the real situation. Among others, the variables of the tax system, tax justice and tax compliance used are thought to have an influence on tax evasion behavior based on the perception of the taxpayer. This research aims to test the mediating role of tax compliance on association between the perceived of the taxation system, tax fairness and tax evasion behavior. The population in this study were 91,224 individual taxpayers at KPP Pratama Karawang Utara. This research used Personally Administered Questionnaires with technique of the Slovin’s Formula in order to obtain a sample size of 100 respondents. This research uses multiple regression models to test each variable on tax evasion. The result showed that the taxation system had a direct effect on tax compliance with a significance value 0f 0.009, tax justice had no direct effect on tax compliance with a significance value 0f 0.841, the taxation system had no direct effect on tax evasion behavior with a significance value of 0.736, tax fairness and tax compliance had a direct effect on tax evasion behavior with a significance value of 0.000 and 0.008, the tax system and tax fairness have an indirect effect on tax evasion behavior through tax compliance with beta values 0.146, and 0.116.